Meeting report: SMART timing—principles of single molecule techniques course at the University of Michigan 2014. Issue 5 (May 2015) - Bartke, Rebecca M.; Cameron, Elizabeth L.; Cristie‐David, Ajitha S.; Custer, Thomas C.; Denies, Maxwell S.; Daher, May; Dhakal, Soma; Ghosh, Soumi; Heinicke, Laurie A.; Hoff, J. Damon; Hou, Qian; Kahlscheuer, Matthew L.; et al.
ABSTRACT: Four days after the announcement of the 2014 Nobel Prize in Chemistry for "the development of super‐resolved fluorescence microscopy" based on single molecule detection, the Single Molecule Analysis in Real‐Time (SMART) Center at the University of Michigan hosted a "Principles of Single Molecule Techniques 2014" course. Through a combination of plenary lectures and an Open House at the SMART Center, the course took a snapshot of a technology with an especially broad and rapidly expanding range of applications in the biomedical and materials sciences. Highlighting the continued rapid emergence of technical and scientific advances, the course underscored just how brightly the future of the single molecule field shines. © 2014 Wiley Periodicals, Inc. Biopolymers 103: 296–302, 2015.